Information Literacy in the Workplace: A Case Study of the Volta River Authority (VRA) Workforce - Agbo, Esther (Ghana Library Journal, 2016)
Underlying the demands and challenges inherent in the 21st century workplace, information literacy is often mistaken for digital literacy. For the most part, those who are digitally literate are generally wizards at using a variety of digital tools, from hardware to software, but are not necessarily information literacy practitioners (i.e. discriminate users of information resources). No matter where you work — in education, healthcare, government, business, and/or industry, making informed decisions means knowing how to access, analyze, synthesize, evaluate, and utilize a variety of information from diverse print and digital resources. Bottom line - to be an effective, informed decision maker in this century, in any workplace, one must know how to integrate and utilize both information and digital literacy practices. The Volta River Authority (VRA) recently introduced the concept of information literacy skills within organization’s business process, through the adoption of an on the job training programme for senior management, middle level managers and supervisors. The programme made provision for lifelong learning schedules such as mentoring, coaching as well as information skill that reflect the 21s’ century information literacy-related competencies that are necessary for readiness of most business organizational workforce. This paper seeks to explore these reflections to workplace information literacy characteristics as captured in existing literature.